Comments on : steady two-dimensional oblique stagnation-point flow towards a stretching surface - Amin, Norsarahaida; Pop, I.; Lok, Y. Y. (The Japan Society of Fluid Mechanics, 2007)
In a recent paper byReza and Gupta(2005)it has been shown that the boundary layer equationsdescribing the two-dimensional oblique stagnation-point flow towards a stretching surface can be reducedto the following two equations: